Changes in Administrative Borders and Their Stability in Lubelskie Region in 1949–2010 - Paweł Cebrykow; Mirosław Krukowski; Mirosław Meksuła; Adrian Zarański (Barometr Regionalny, 2013)
The article presents the problem of changes in administrative borders in the Lubelskie region throughout the past 60 years, since the end of World War II. In this period Poland experienced four major reforms that transformed the system and structure of administrative division. In five periods between the reforms there were also certain minor changes along the national borders. The analysis of changes was primarily based on cartographic materials presenting the administrative divisions, which allowed for efficient analyses of the border routes. Using the archive maps the authors prepared analytical maps from 8 temporal perspectives. Consequently, synthetic maps presenting all the observed changes in voivodship (Polish: województwo), county (Polish: powiat) and commune (Polish: gmina) borders were drafted. Such materials were the base for preparing the final maps illustrating the stability of the border routes between voivodships, counties and communes. The analyses of the materials allowed number of conclusions to be drawn. Firstly, the borders of Lubelskie Voivodship are relatively stable, particularly the fragments which run along the Vistula and the Bug Rivers. In the case of county borders, their permanence is much lower. At the lowest level of administrative division, variability is the highest, yet the share of permanent borders reaches 40%. Generally, it can be stated that the higher the level of administrative division, the higher the stability of borders. The present article may constitute a basis for further research on the causes and effects of borders between administrative units. Along with the analysis of border permanence, another problem that the authors addressed is the method of linear presentation of object changes. In order to analyse border changes effectively, the authors propose an indirect presentation of border stability by showing the stability of the area marked within these borders. Such a device substitutes the troublesome analysis of overlapping linear structure with an analysis of a clearer image of stability, presented with contour lines.